PENGARUH FINANCIAL TECHNOLOGY TERHADAP PENDAPATAN USAHA KECIL DAN MENENGAH DI DESA LANDUNGSARI KECAMATAN DAU KABUPATEN MALANG - Nurvenia, Nurvenia; Abdullah , Mohammad Faisal (Program Studi Ekonomi Pembangunan, 2021)
This study aims to find out the Effect of Financial Tehnology on Small BusinessIncome. The type of data used in this study is a type of Primary data that is qualitative and quantitative. Sampling techniques using purposive sampling techniques with a total of 50 respondents. The data analysis technique used is the Multiple Linear Regression method. The results in this study are partially Digital Payments positively and significantly affect the income of small businesses in the village of Landungsari Subdistrict Dau Malang, Financial Management has a positive and significant effect on the income of small businesses in the village landungsari Subdistrict Dau Malang. Then simultaneously, Digital Payments and Financial Management has positively and significantly affect the income of small businesses in the village of Landungsari Subdistrict Dau Malang.